Percepção dos consumidores e profissionais de saúde sobre a produção de suínos e pesquisa de Salmonella sp. em carne suína no estado de Goiás - Teixeira, Karla Andrade (2021)
Although pork is one of the most consumed in the world, its consumption in Brazil is still low compared to other countries and other types of meat.However, when we look at pork consumption data by Brazilian state, it appears that Goiás stands out with an average consumption higher than the national one and with potential for increase. Thus, it is necessary to first understand the consumer's profile and his perspective on pork. Due to the greater access to information that the current consumer has, a multiplicity of variables or attributes present in a product influence the decision-making process of purchase and consumption, in addition, it can also be influenced by opinion makers such as health professionals. Consumers, when buying the product, are more concerned with aspects related to their health, the quality of the product in relation to the presence of possible contaminants and residues, and some are concerned with the way of production and slaughter of these animals and their well-being. In terms of quality, a major concern is the microbiological quality of the meat, since it can be contaminated with different types of pathogens, among them Salmonella sp .. Which is an important transmitter of foodborne diseases (DTAs). From this context, two surveys were carried out. The first with 361 people from the state of Goiás. By means of an electronic questionnaire with 38 questions, to know beyond the profile the consumer's perception regarding consumption habits, healthiness, quality, production system, and animal welfare. The second was carried out with 90 health professionals, in order to get to know the point of view about pork and what they recommend about it to their patients / clients. The professionals answered 15 questions. A study was also carried out to verify the presence of Salmonella sp. in meat sold in commercial points in the city of Goiânia (GO). 60 samples of fresh meat (sirloin and ham) and 40 samples of industrialized meat (sausage and ham) were collected and processed and analyzed. Samples with the presence of Salmonella sp. underwent an antimicrobial susceptibility profile analysis, 9 bases were tested. It was noticed that the profile of the people who participated in the research is quite varied and that there are still the presence of myths, doubts and misconceptions in all aspects addressed, therefore, there is a need to work on these aspects, and it is possible to do so draw up educational plans. The results obtained with the participating health professionals demonstrated that the misinformation among them still exists, especially regarding the nutritional value, the health and hygiene of pork. Thus, as it is an opinion-forming public, it is imperative that actions are developed in order to bring more information about the entire production process of the pig chain. From meat samples 16.75% of shank and 10% of loin were positive for the presence of Salmonella sp. Of the isolates, 100% showed resistance to any of the tested antibiotics and 87.5% showed multidrug resistance.